Go for Python Developers - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
The Go programming language is becoming more popular these days with cloud-native applications and the Kubernetes ecosystem. If you are coming from Python, you will find yourself surprised to see similar patterns, while at the same time see some things that are missing or plain impossible with Go. In this course, I will introduce you to some of the basics of Golang from a Python perspective, so that you can reduce the friction trying to learn it. Topics include: * Packages, imports and variable definitions * From lists to arrays and slices * From Python dictionaries to Go maps * Looping on data structures, retrieving and adding values or items * Error handling, and the surprising fact that there aren't any tracebacks or exceptions in Go A few resources that are helpful if you are trying to learn Go, some of them covered in the course: * Visual Studio Code for Go * The Go playground * An (interactive) tour of Go.